The Use of Informal Language in Thesis Proposal: An Analysis Of EFL University Students’ Writings - Dhandi, Yumnanita Putri; Madjid, Hilda Izzati (ICONELT, 2022)
Informal languages are often used in ordinary and casual communication in both written and spoken forms, but it is inappropriate if individuals use informal language in academic writing. In some cases, students still use informal expressions in academic writing such as thesis proposals. This study identified the use of informal languages in students’ thesis proposals. Specifically, the study examined the elements of informality and types of informal languages that students frequently use when writing a thesis proposal. By using a qualitative method, this study analyzed 15 students’ thesis proposals. The findings found that there are seven elements of informality covering pronouns, conjunction, listing expressions, contraction, adverbs, segment fragment, and direct questions. The types of informal language that students frequently use are pronouns, conjunctions, and listing expressions. The findings further indicate that the use of informal language is not only at a morphological but also syntactic level.